Optimizing patient engagement to enhance a learning health system - Mork, Mikie; Strilchuk, Allison; Patel, Jatin N.; Smith, Donna; Wilkinson, Gloria; Brown, Adam; Kromm, Seija; Dyson, Michele; Wasylak, Tracy (Frontiers in Health Services, 2025)
BackgroundPatient and family advisors have served as an integral part of a collaborative, province-wide learning health system in Alberta for more than a decade, contributing to evidence generation, knowledge mobilization and research activities focused on improving patient outcomes.ObjectiveThis paper describes how Alberta Health Services (AHS) and the Strategic Clinical Networks™ (SCNs™) (i) embedded patient engagement and patient-oriented research in health services innovation and improvement, including project planning, co-design, execution and decision-making, (ii) created opportunities for patient advisors to participate in leadership committees, research panels and keynote addresses, (iii) co-designed engagement practices, resources and supports with patients and community partners, and (iv) applied a mixed-methods approach for assessing engagement effectiveness.MethodsAHS patient advisors collaborated with provincial partners and researchers, including the Alberta Strategy for Patient-Oriented Research (SPOR) Support Unit (AbSPORU) Patient Engagement Team, to co-design and pilot a standardized set of patient and family engagement indicators (PFE-Is) that could be used to evaluate engagement effectiveness and improve current practices. Through surveys and consultations with key interest holders, the team established a baseline for effective engagement and built consensus for patient engagement priorities, recommendations, and actions to improve patient and family engagement.ResultsFive themes emerged from consultations with advisors and AHS staff: supports for engagement, learning together, diversity of perspectives, the role of advisors, and evaluating meaningful patient engagement. Recommendations and actions to strengthen patient engagement emerged that build on existing practices and supports, and include opportunities to improve resources, foster inclusivity, and promote collaborative learning opportunities.DiscussionThe evidence-based PFE-Is and survey are ready for implementation across Alberta's health system to monitor and evaluate patient and family engagement, gather feedback from advisors and staff, and refine current strategies and practices. Continued collaboration with patient and family advisors is expected to support progress as a learning health system and strengthen the ability of provincial health agencies to generate actionable insights, drive improvements, and deliver high quality, patient-centred care.